EGFR Signaling Networks in Cancer Therapy - Haley, John D.; Gullick, William John.; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2008)
The epidermal growth factor (EGF) receptor and its downstream signal transduction networks have been implicated in the ontology and maintenance of tumor tissues, which has motivated the discovery and development of molecularly targeted anti-EGFR therapies. Edited by John Haley and William J. Gullick, EGFR Signaling Networks in Cancer Therapy, is separated into two sections. The first of which probes the molecular pathways and the intersection of signaling networks which are frequently deregulated in human cancers, with a view to describing EGF receptor in a tumor tissue specific context. Meanwhile, the second section illustrates the many ways in which EGF receptor contribute to abnormal survival and migration signaling in cancer cells and to epithelial to mesenchymal transition and metastasis. The book also describes the mitogenic, survival, adhesive and migratory pathways within a framework of interacting subsystems that contribute to the activity and physiological regulation of the receptor in normal and neoplastic tissues. Even though there is still much to learn, this volume explores this fascinating system with compelling information.
EGFR Signaling Networks -- EGFR Receptor Family Extracellular Domain Structures and Functions -- EGFR family heterodimers in cancer pathogenesis and treatment -- Structure-function of EGFR kinase domain and its inhibitors -- Internalization and degradation of EGF receptor -- Differential dependence of EGFR and ErbB2 on the molecular chaperone Hsp90 -- Activation of STATs 3 and 5 Through the EGFR Signaling Axis -- The intersection of EGFR and the Ras signaling pathway -- PHOSPHOINOSITIDE 3-KINASE ENZYMES AS DOWNSTREAM TARGETS OF THE EGF RECEPTOR -- Convergence of EGF Receptor and Src Family Signaling Networks in Cancer -- A Molecular Crosstalk between E-cadherin and EGFR Signaling Networks -- Crosstalk Between Insulin-like Growth Factor (IGF) and Epidermal Growth Factor (EGF) Receptors -- Negative regulation of signaling by the EGFR family -- Nuclear ErbB Receptors: Pathways and Functions -- Temporal Dynamics of EGF Receptor Signaling by Quantitative Proteomics -- Computational and Mathematical Modelling of the EGF Receptor System -- EGFR in Tumorigenesis and EGFR Tyrosine Kinase Inhibitors in Cancer Therapy -- Expression and prognostic significance of the EGFR in solid tumors -- Signalling by the EGF receptor in human cancers: accentuate the positive, eliminate the negative -- EGFR signaling in invasion, angiogenesis and metastasis -- Constitutive activation of truncated EGF receptors in glioblastoma -- EGFR Mutations, Other Molecular Alterations Related To Sensitivity to EGFR Inhibitors, and Molecular Testing for EGFR-Targeted Therapies in Non-Small Cell Lung Cancer -- Crosstalk Between COX-2 and EGFR: A Potential Therapeutic Opportunity -- Cellular sensitivity to EGF receptor inhibitors -- Utilizing combinations of molecular targeted agents to sensitize tumor cells to EGFR inhibitors.
Keywords: Medicine; Cancer research; Oncology; Medicine & Public Health; Oncology; Cancer Research; Electronic books